The candy house [book club bag] - Egan, Jennifer (Scribner, 2023)
The Candy House opens with the staggeringly brilliant Bix Bouton, whose company, Mandala, is so successful that he is 'one of those tech demi-gods with whom we're all on a first name basis.' Bix is 40, with four kids, restless, desperate for a new idea, when he stumbles into a conversation group, mostly Columbia professors, one of whom is experimenting with downloading or 'externalizing' memory. It's 2010. Within a decade, Bix's new technology, 'Own Your Unconscious'--That allows you access to every memory you've ever had, and to share every memory in exchange for access to the memories of others--has seduced multitudes. But not everyone. Egan spins out the consequences of Own Your Unconscious through the lives of multiple characters whose paths intersect over several decades...The Candy House is also a testament to the tenacity and transcendence of human longing for real connection, family, privacy, and love. --